2019
DOI: 10.1002/hon.2635
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Philadelphia‐negative myeloproliferative neoplasms in accelerated/blastic phase with azacytidine. Clinical results and identification of prognostic factors

Abstract: There have been some reports on a possible role of azacytidine (AZA) in the treatment of accelerated/blastic phase evolved from Philadelphia‐negative myeloproliferative neoplasms (MPN‐AP/BP), but results are conflicting. In this study, we analyzed a cohort of 39 patients with MPN‐AP/BP treated frontline with AZA at the standard dosage (75 mg/m2). Median time from diagnosis to AP/BP evolution was 92.3 months (IR 29.9‐180.1). All patients were evaluable for hematologic response: two patients (5.2%) died early af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The provisionally defined subgroup of accelerated-phase myelofibrosis used a 10% blast cutoff arbitrarily based on limited retrospective data. 21 Some studies suggest that acceleratedphase should be treated more aggressively, for example, including hypomethylating agents, 11,22,23 aiming to delay the time to leukemic transformation, and to also implement curative therapies (stem cell transplantation) in fit patients. This is the first study to evaluate outcome for accelerated-phase myelofibrosis undergoing curative treatment with reduced intensity allogeneic stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The provisionally defined subgroup of accelerated-phase myelofibrosis used a 10% blast cutoff arbitrarily based on limited retrospective data. 21 Some studies suggest that acceleratedphase should be treated more aggressively, for example, including hypomethylating agents, 11,22,23 aiming to delay the time to leukemic transformation, and to also implement curative therapies (stem cell transplantation) in fit patients. This is the first study to evaluate outcome for accelerated-phase myelofibrosis undergoing curative treatment with reduced intensity allogeneic stem cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis of 19 MPN patients (developing MPN-BP) who were treated with azacitidine showed that 5 patients (26.3%) achieved CR, 1 had a partial response, 4 had stable disease, and 3 displayed hematological improvement; since the time of BP evolution, the median cumulative survival was 9.9 months [104]. Andriani and colleagues [105] conducted another recent retrospective study in 39 patients who were in MPN-AP/BP and were treated with azacitidine in the frontline setting at 10 hematologic centers in Italy. Hematologic responses were noted in 24 patients: 8 (20.5%) and 7 (17.9%) achieved complete and partial responses, respectively, whereas hematologic improvement was noted in 9 (23.1%); 4 responders underwent allo-HSCT.…”
Section: Therapeutic Modalitiesmentioning
confidence: 99%
“…Hematologic responses were noted in 24 patients: 8 (20.5%) and 7 (17.9%) achieved complete and partial responses, respectively, whereas hematologic improvement was noted in 9 (23.1%); 4 responders underwent allo-HSCT. The overall response rate was 61.5%, and the entire cohort had a median OS of 13.5 months; the median OS for responders was about 4 months longer (17.6 months) [105]. Another phase 1b study evaluated the safety and maximum tolerated dose of ruxolitinib in combination with azacitidine in a small cohort of patients comprising 7 with MPN-AP (including MDS) and 7 with MPN-BP.…”
Section: Therapeutic Modalitiesmentioning
confidence: 99%
“…To date, therapeutic options for patients with aCML are limited, and although therapy with ruxolitinib can be associated with responses in patients with CSF3R mutations, 5,12,13 particularly in the absence of SETBP1 mutations, there is insufficient evidence on the optimal therapeutic strategies for these patients. Although several reports including small patient cohorts have described the potential use of hypomethylating agents (HMAs) such as decitabine and azacitidine for the treatment of aCML, 3,14‐18 an evaluation of the survival benefit or clinical activity of these compounds in a larger cohort and a comparison with other therapeutic approaches are needed.…”
Section: Introductionmentioning
confidence: 99%